Clinical and hematological features of childhood immune thrombocytopenia at pediatric center of Hue central hospital - Tuy, Nguyen Van; An, Do Doan Thuan (Tạp chí Y học lâm sàng Bệnh viện Trung Ương Huế, 2025)
ABSTRACT Background: Immune thrombocytopenia (ITP) is the most common of the hemorrhagic diseases caused by thrombocytopenia in children. It usually occurs between the ages of 5 and 7 years old and at both sexes. It is difficult to predict ITP basing on bleeding because some severe thrombocytopenia cases have slight purpura or ecchymoses. This study aims to describe the clinical and hematological features of childhood immune thrombocytopenia Methods: This was a cross - sectional study. Patients were stratified according to age (0 to 15 years) and diagnosed ITP at the Pediatric Center of Hue central Hospital. Results: From May 2020 to March 2021, we identified 42 children diagnosed with idiopathic thrombocytopenia. Newly diagnosed ITP was the most common (66.7%) followed by chronic ITP (26.2%) and persistent ITP (7.1%). There was a slight predominance of boys to girls with the male - to - female ratio was 2:1. However, this ratio was dependent on ITP phases. The highest prevalence of immune thrombocytopenia was found under 6 years old. Children in this study usually had a history of preceding infection or vaccination. Natural hemorrhage was 83.3% (skin 95.2%). The most common type of cutaneous bleeding was petechiae (83.3%). Mild to moderate hemorrhages were dominant. Newly diagnosed ITP had less severity of hemorrhage than persistent and chronic ITP. Most children did not have a fever, hepatomegaly, splenomegaly, and lymphadenopathy. The majority of children seem to have severe thrombopenia (66.7%), but the number of platelets was not related to the severity of bleeding. Mean platelet volume was normal. Conclusions: Newly diagnosed ITP was the most common. There was a little clinical and hematological features difference between the ITP phases.